A1 New starts and directions: understanding the role of hidden expansion proteins in HD. (13th September 2016) - Bañez-Coronel, Monica; Ayhan, Fatma; Tarabochia, Alex D; Zu, Tao; Perez, Barbara A; Tusi, Solaleh Khoramian; Pletnikova, Olga; Borchelt, David R; Ross, Christopher A; Margolis, Russell L; T Yachnis, Anthony; Troncoso, Juan C; et al.
Abstract : Huntington's disease (HD) is caused by a CAG CTG expansion in the huntingtin (HTT) gene. While most research has focused on the HTT polyGln-expansion protein, we recently reported that four additional, novel, homopolymeric expansion proteins (polyAla, polySer, polyLeu, polyCys) accumulate in HD human brains. These sense and antisense repeat-associated non-ATG (RAN) translation proteins accumulate most abundantly in brain regions with neuronal loss, microglial activation and apoptosis, including caudate/putamen, white matter, and in juvenile-onset cases, also the cerebellum. RAN protein accumulation and aggregation patterns are length-dependent. Codon substitution experiments show HD-RAN proteins are toxic to neural cells independent of RNA effects. These data support an important role for RAN proteins in HD, and suggest that therapeutic strategies targeting both sense and antisense transcripts, RAN proteins or RAN translation may be important for treating HD patients. We are currently using mouse models of HD to understand the time-course and impact that HD-RAN proteins play in disease and also to examine which models best mimic the findings we have seen in human autopsy patients. The discovery of HD RAN proteins was the first demonstration that RAN translation can occur across an expansion located in an open reading frame and suggests RAN translation may also contribute to other polyglutamine diseases. Recent efforts to understand the mechanisms of RAN translation and insights into the roles that RNA gain of function and RAN mechanisms play in HD as well as ALS/FTD, ataxia and myotonic dystrophy will be discussed.